Analysis of the relative supercooling enhancement of two emerging supercooling techniques - Ștefan-Ioan Câmpean; George-Andrei Beșchea; Alexandru Șerban; Matthew J. Powell-Palm; Boris Rubinsky; Gabriel Năstase (AIP Advances, 2021)
We present herein an experimental study on the ice-nucleation kinetics of two recently introduced aqueous supercooling modalities—oil-sealed isobaric supercooling and isochoric supercooling. A series of constant-cooling rate experiments compare the apparent nucleation temperatures of pure water supercooled under these modalities with conventional open-air isobaric supercooling, demonstrating that both methods significantly enhance the supercoolability of the system as compared to open-air supercooling. However, while the mean nucleation temperatures of the two methods are statistically comparable, isochoric supercooling displays approximately half the variability of isobaric oil-sealed supercooling, which may have important implications on the design of supercooling-based biopreservation protocols in which stability and reproducibility are paramount.